К ВОПРОСУ О ПОНЯТИИ ЭКОЛОГИЧЕСКОГО НОРМИРОВАНИЯ (Journal of actual problems of jurisprudence, 2019)
The author of this article examines environmental regulation and concludes that the valuation of environmental quality is one of the elements ofpublic administration in the field of ecology.